Reflections about continuing teachers formation in contemporaneity (Research, Society and Development, 2020)
Even living in contemporary times, through the resignifications of society, culture, teaching and learning, pedagogical practices still seem to continue not to correspond with these transformations. In this sense, the school and education professionals are invited to review their social and pedagogical role to better meet the needs of students and the demands of the school. This qualitative article aims to reflect on the role of the teacher in relation to the teaching and learning processes in contemporary times, going through the bias of continuing teacher education. Through bibliographic research supported by theorists who deal with the theme like as: Freire, Prado & Cunha, Mercado, Moran, Nóvoa, Nunes, Schimitt and Shõn understand that it is not feasible to remain with the same practices, in a space and time that have changed with globalization, which are in a continuous movement of remodeling. We understand that the teaching and learning processes need to be based on reflective teaching, allowing teachers and students to collectively and collaboratively build actions and reflections that lead them to seek knowledge, placing everyone as eternal learners.